Economic Analysis of Maximum Cross-Section of Submarine Cables for 66 kV Offshore Wind Farm Collection Systems - Chaohui WANG; Songge HUANG; Bin LIN; Yuwei CHEN; Shumin FAN; Zhaohui SHI (Zhongguo dianli)
Topology optimization design of the maximum submarine cable cross-section for offshore wind farm collection systems is an effective means to reduce the total investment of the offshore wind farms and improve the transmission efficiency and system reliability. Since the collection system pooling network has various types of topology and the constraints for selecting the maximum submarine cable cross-section are not considered in the existing optimization studies, there exist low efficiency and high difficulty in the non-convex and non-linear optimization search process of collection system topology, and it is difficult to obtain a global optimal layout scheme. To this end, we propose an economic analysis method for selection of the maximum submarine cable cross-section for 66 kV offshore wind farm collection systems. The constraints for selecting the optimal submarine cable maximum cross-section are added in the process of topology optimization of collection systems through uniparental genetic algorithm and minimum spanning tree technique (MST) to reduce the search space, improve the search accuracy and accelerate the search speed. The results of case study show that it has a significant impact on the economic optimization results to consider the selection constraints of the maximum submarine cable cross-section in the planning of collection system.